Apakah Kepedulian Lingkungan dan Perceived Quality-Benefit Mendorong Keinginan Konsumen Membayar Lebih Banyak untuk Produk Pro-Lingkungan? - Cahyasita, Dhika; Aisyah, Dinda Dewi; Sari, Ayu Kumala (Jurnal Sosial Ekonomi Pertanian, 2024)
This research aims to see the influence of environmental awareness and quality benefits consumers feel on willingness to pay more. Data from 228 respondents was collected through an online survey to fill out a structured questionnaire. The PLS-SEM approach was used in data analysis. The results of the study show that both environmental awareness and perceived quality-benefit have a significant positive influence on consumers' willingness to pay more for green products. The policy implication that can be recommended is to normalize premium prices for pro-environmental products by optimizing marketing communications.